Analisa Permasalahan Belajar Bahasa Inggris Siswa pada Masa Covid-19 di Sekolah Menengah Kejuruan - Grace Novenasari Manurung; Fadhilah Zamzam (Jurnal Kreatif Online, 2023)
The learning process during the Covid-19 pandemic was carried out online at all levels of education. Online learning makes the use of information technology becomes the concern for teachers, students, and parents. This study aims to analyze the problems faced or experienced by students when learning English during the Covid-19 era. This study uses a survey research design. The population of the study were students of SMK Mandalasila Palu while the research subjects were students of Class XI. The convenience sampling technique was used to choose 25 students as the research sample. Data was collected using a questionnaire then the data were analyzed descriptively. The analysis of the data revealed three issues that students in the Covid-19 era encountered when studying online, technical issues, issues with the teaching and learning process, and external issues. Internet network and application utilization difficulties are the most significant technical problems. Student independence, application of learning processes, tasks, and student inactivity are some of the issues with learning and teaching. External issues include students' incapacity to provide internet quota, as well as the state of their home during the online learning process. The findings of this study suggest that it is crucial to invest in the infrastructure and facilities needed to enable online learning, both at schools and in the areas where students reside.